Design, Synthesis, and Potential Antidepressant‐like Activity of 7‐prenyloxy‐2, 3‐dihydroflavanone Derivatives. (26th January 2016) - Zhen, Xing‐Hua; Quan, Ying‐Chun; Peng, Zhou; Han, Yan; Zheng, Zhou‐Jun; Guan, Li‐Ping
Abstract : A series of 7‐prenyloxy‐2, 3‐dihydroflavanone derivatives were synthesized and screened for their antidepressant‐like activity. Among them, it was observed that compounds5j and5k were found to be the most antidepressant‐like activity. In addition, it was found that compounds5j and5k significantly increased the concentrations of the main neurotransmitters 5‐HT and NE in the hippocampus, hypothalamus, and cortex. Compounds5j and5k also significantly increased the contents of 5‐HIAA in the hippocampus and cortex, shut down 5‐HT metabolism compared with mice treated with stress vehicle. These results suggested that compounds5j and5k displayed potent antidepressant‐like properties that were mediated via neurochemical systems. Abstract : A series of 7‐prenyloxy‐2, 3‐ dihydroflavanone derivatives were synthesized and screened for their antidepressant‐like activity. Compounds5j and5k were found to be the most antidepressant activity. The results suggested that compounds5j and5k possessed potent antidepressant‐like properties that were mediated via neurochemical systems.